2014
DOI: 10.1111/mmi.12762
|View full text |Cite
|
Sign up to set email alerts
|

Dominant negative mutant of PlasmodiumRad51 causes reduced parasite burden in host by abrogating DNA double‐strand break repair

Abstract: SummaryMalaria parasites survive through repairing a plethora of DNA double-stranded breaks (DSBs) experienced during their asexual growth. In Plasmodium Rad51 mediated homologous recombination (HR) mechanism and homology-independent alternative endjoining mechanism have been identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…Yet, in B. bovis orthologs may be identified only for RPA, Rad51, and Rad54, and many similar examples of "missing" proteins hold [13,31], suggesting the merging of functions. In this study, we wished to understand the contributions of BbRad51 to SGC because proteins of this family are considered essential to HR and gene conversion in other systems, including other apicomplexans [29,40]. Our prior identification of This parasite instead may depend upon a synthesis-dependent microhomologymediated end-joining mechanism like that demonstrated in P. falciparum [42], but this remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, in B. bovis orthologs may be identified only for RPA, Rad51, and Rad54, and many similar examples of "missing" proteins hold [13,31], suggesting the merging of functions. In this study, we wished to understand the contributions of BbRad51 to SGC because proteins of this family are considered essential to HR and gene conversion in other systems, including other apicomplexans [29,40]. Our prior identification of This parasite instead may depend upon a synthesis-dependent microhomologymediated end-joining mechanism like that demonstrated in P. falciparum [42], but this remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Organisms with defective Rad51 consistently suffer reduced viability and enhanced sensitivity to environmental insult [24][25][26][27][28][29]. For example, knockout of the Rad51 gene in mice resulted in embryonic lethality [30], whereas loss of the Tbrad51 gene in the kinetoplastid parasite, Trypanosoma brucei, yielded parasites that were compromised in growth and hypersensitive to methyl methanesulfonate (MMS) [28].…”
Section: Introductionmentioning
confidence: 99%
“…Some reports which have shown that BER, MMR and DNA doublestrand break repair (DSBR) pathways are somehow linked to drug resistance in P. falciparum and some of the proteins involved in these pathways can be the new anti-malarial drug targets [21][22][23][24]. Several non-synonymous single nucleotide polymorphisms (SNPs) in the MMR genes of artemisnin drug resistant strains in P. falciparum have been reported [15].…”
Section: Introductionmentioning
confidence: 98%
“…PfRad51. This study demonstrated that parasite exclusively relies on the HR repair pathways for DSBs repair (54). Although, it has been reported previously that DNA damage can induce up-regulation of PfRad51 and PfRad54, but how does HR repair machinery recognizes DSBs in the parasite has yet to be studied (52).…”
Section: Double-strand Break Repair Pathways (Dsbr)mentioning
confidence: 63%
“…It has been shown that the parasite mostly utilizes the homologous recombination repair (HR) system to repair its double-strand breaks, which are the most deleterious forms of genetic aberrations, which in turn can lead to cell death (54). It is believed that the parasite lacks the machinery for canonical NHEJ repair system (7).…”
Section: Introductionmentioning
confidence: 99%